Analysis Of The Use Of Office Facilities At Pt. Pos Indonesia - Joko Murtiyanto, Muhammad Ajib Albana; Christian Wiradendi Wolor; Marsofiyati (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This study aims to determine how the use of office facilities at PT POS INDONESIA LAPANGAN BANTENG, to find out the constraints of facilities at PT POS INDONESIA LAPANGAN BANTENG, and also solutions to overcome the obstacles faced when using office facilities at PT POS INDONESIA LAPANGAN BANTENG. This research uses a qualitative method with a descriptive approach that describes and analyzes the conditions that occur. Qualitative research is based on primary and secondary data. In collecting data sources, researchers collect data in the form of primary data and secondary data. Primary data in the study were obtained through observation, interviews and documentation, while secondary data were obtained through journals, articles, and books related to the study. Based on the results of the research that has been done, it can be seen that the use of facilities at the PT POS Indonesia office is quite good, but not all office facilities have received sufficient attention in terms of maintenance. This can be seen from the damaged items that do not immediately get treatment and are only placed next to the office while waiting for the technician to come to repair.